1990
DOI: 10.1111/j.1365-2044.1990.tb14683.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnanolone emulsion A preliminary pharmacokinetic and pharmacodynamic study of a new intravenous anaesthetic agent

Abstract: SummaryFigdor et al.' demonstrated in 1957 that a series of structurally related pregnanes, without notable endocrine action, were anaesthetically active when administered to mice. The most active of these pregnanes was pregnanolone (3a-hydroxy-5/l-pregnane-20-one), which is a naturally occurring metabolite of progesterone, first isolated from urine of pregnant women in 1937.' The anaesthetic effect of pregnanolone has been demonstrated in several animal speciesZ3 but its lack of water solubility prevented its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…In animal studies, it is shown that some of the effects of alcohol are mediated via increased productions of allopregnanolone [10, 24, 25]. In humans, a high dose of pregnanolone is hypnotic and anesthetic [1, 26]. In parallel with inducing sedation, allopregnanolone has also been shown to induce disturbances in motor function [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, it is shown that some of the effects of alcohol are mediated via increased productions of allopregnanolone [10, 24, 25]. In humans, a high dose of pregnanolone is hypnotic and anesthetic [1, 26]. In parallel with inducing sedation, allopregnanolone has also been shown to induce disturbances in motor function [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Administered intravenously in doses of 0.4–0.6 mg/kg, it produces anesthesia of short duration with minimal effects on hemodynamic and respiratory parameters [9]. Pregnanolone has also been reported to have hypnotic activity [10] and basic research on this class of compounds has demonstrated that compounds closely related to pregnanolone possess hypnotic [11], antiepileptic [12] and anxiolytic activity [13]. Brain and plasma levels of allopregnanolone (3α-hydroxy-5α-pregnan-20-one) temporally follow circulating levels of progesterone produced by the corpus luteum [14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, alphaxalone has been used successfully as an intravenous sedative-hypnotic in human subjects [8]. Like alphaxalone, preliminary human pharmacodynamic and pharmacokinetic studies reveal that pregnanolone is capable of inducing anesthesia of short duration (plasma ti/2 = 0.9-1.4 h) after intravenous infusion [9], The anes thetic effect was accompanied by minimal effects on hemodynamic and respiratory parameters although exci tation of short duration was observed during induction. The evaluation of pregnanolone as an orally administered sedative-hypnotic agent has been hampered by its low water solubility.…”
Section: Introductionmentioning
confidence: 99%